Classification and Prediction of Smoking Behavior and Hypertension in the Healthy Family Program with R (Case Study : Bali Provincial Government Department of Health) - I Gede Abi Yodita Utama; Nyoman Pramaita; Made Sudarma (International Journal of Engineering and Emerging Technology, 2020)
The Healthy Indonesia Program with the Family Approach aims to improve the quality of human life and is a government program that starts from the family environment. There are 12 indicators marking the health status of a family. The Provincial Government of Bali in implementing the 12 indicators there are two main problems of non-communicable diseases, namely patients with hypertension and smoking behavior. An analysis in the form of classification and prediction is needed to overcome these problems. Classification and prediction is one of the techniques in data mining. Through R, a decision tree can be produced which can be used to help the classification process and produce predictions related to the problem of non-communicable diseases. The decision tree results can be predicted that the dominant hypertension are in the age group classification of 20-40 years and 41-70 years with a probability of 0.14. As for smoking behavior, the highest smoking tendency was obtained in the classification of male sex whose status worked with a probability of 0.44.